Knowledge, skills and attitudes of doctors towards assessing cognition in older patients in the emergency department. - KENNELLY, SEAN; O'NEILL, DESMOND (My University, 2013)
PURPOSE OF THE STUDY: Although cognitive impairment and delirium are highly prevalent in older patients who present to the emergency department, multiple studies have highlighted inadequate detection by doctors. This study investigated potential reasons underlying this. STUDY DESIGN: A 14-item self-administered questionnaire was distributed to all medical, surgical and emergency department physicians involved in the care of older patients in the emergency department of an urban university teaching hospital between January and March 2012. RESULTS: The questionnaire was completed by 76/97 (78%) of eligible respondents. Respondents reported screening an average of one in four older patients that they reviewed. Almost one-third (22/76, 29%) felt they lacked the relevant expertise to perform cognitive screening: those with training in geriatrics were less likely to cite lack of expertise as a factor. While the majority felt screening for cognition in the emergency department-setting was important (59/76, 78%), several limiting factors were identified: lack of a screening tool; lack of privacy; too much noise; and time constraints. There was no consensus on who should perform screening. CONCLUSIONS: Doctors reviewing patients in the emergency department-setting reported several important factors limiting their ability to screen older patients for cognitive impairment. Respondents to this questionnaire did not feel the emergency department environment was conducive towards the assessment of cognition in older patients. Clarification of each discipline's responsibility in the detection, assessment and management of delirium and/or dementia, and the implementation of emergency department cognitive screening instruments more suited to this setting would likely improve detection and management.
PUBLISHED
Keywords: Elderly patients; Ageing; Neuroscience